2001
DOI: 10.1073/pnas.191381798
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the peptide backbone largely defines the thermodynamic propensity scale of residues at the C′ position of the C-capping box of α-helices

Abstract: The C position of the C-capping box is the second residue outside of the helix. Statistical analysis of residue distribution at the C position in the ␣-helices' C-capping box showed that different amino acid residues occur with different probabilities, with the strongest preference being for glycine. To understand the physicochemical basis for this preference, we studied the effects that 17 amino acid substitutions at the C position in an ␣-helix of ubiquitin have on the stability of this protein. We determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 40 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…The ␤-branching of amino acid residues has been proposed to lead to a larger burial of the polar backbone in the helical state (19). This suggestion was later supported by experimental and theoretical considerations (6,37,38,40,41). The observed low enthalpy for the ␤-branched residues (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The ␤-branching of amino acid residues has been proposed to lead to a larger burial of the polar backbone in the helical state (19). This suggestion was later supported by experimental and theoretical considerations (6,37,38,40,41). The observed low enthalpy for the ␤-branched residues (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Assuming that the activation energy for irreversible denaturation of I-E k -Hb βH81Y is large, as observed in the I-E k -Hb wild-type (22), the thermodynamic parameters were analyzed as an equilibrium quantity, and are summarized in To analyze the thermodynamic origin of the stability difference, the thermodynamic parameters at the reference temperature, 75.4 C, the denaturation temperature of the I-E k -Hb wild-type at pH 5.5, were calculated using its ∆C p values, 11.1 kJ mol Ϫ1 K Ϫ1 for the mildly acidic pH and 15.9 kJ mol Ϫ1 K Ϫ1 for the neutral pH (22), on the assumption that those of the I-E k -Hb βH81Y mutant are similar (Table 2). Within this narrow temperature range, the extrapolation error should be small (24). The results clearly showed that the decreased stability caused by the βH81Y mutation is due to the decreased ∆H, and is partially compensated by the decreased ∆S, while the increased stability at pH 5.5 relative to pH 7.4 is due to the decreased ∆S, similar to the I-E k -Hb wild-type.…”
Section: Resultsmentioning
confidence: 80%
“…When compared with published data for N34(L6)C28, N34(L6)C28-HIS has a 4°C higher melting temperature. We speculate that addition of the Cterminal tag promotes stability by attenuating the helix dipole moment or by reducing fraying of the helical ends (19,22).…”
Section: Design Of Four Allelic Series-residuesmentioning
confidence: 99%